Hugo Kołłątaj, a State Prisoner in Olomouc a Josefov in 1794–1802 - Sobotková, Marie (Poznańskie Studia Slawistyczne, 2018)
The Kraków canon priest Hugo Kołłątaj (1750–1812), one of the authors of the Polish Constitution of 3rd May 1791, a writer, philosopher and teacher, the rector of the Jagiellonian University and the Vice-Chancellor of the Polish-Lithuanian Union, endeavoured to escape to Venice via Galicia and Hungary after the defeat of Kościuszko’s uprising. He was, however, captured by the Austrians in Radymno on 6th December 1794 and then imprisoned in Przemyśl. On 19th December of the same year, Kołłątaj was transported to Olomouc, where he was interned as state prisoner no. 4. From 14th February 1795 to 29th June 1798, he was imprisoned in the Josefov fortress and he then returned again to Olomouc. Kołłątaj was forced to remain at the Olomouc Jesuit Barracks until 6th December 1802 and he departed Olomouc on 19th December of the same year. During his internment, he wrote elegiac verse and scientific works dedicated to anthropogeography, history, ethnography and ethics.The memorial plaque to Hugo Kołłątaj, produced according to an artistic design by Marek Mielczarek and placed on the façade of the Czech Army’s Administrative Archive in Olomouc at the initiative of the Ministry of Culture and National Heritage of the Republic of Poland, was unveiled on 20th October 2015 as a permanent reminder of the legacy of this leading Polish enlightenment figure.